Politics of the USA in Post-Soviet Central Asia: character and prospects - A. A. Каzаntsev (Vestnik MGIMO-Universiteta)
Four main periods can be distinguished in US policy in Central Asia. In the first half of the 1990-s the relations with Russia were a priority, and the region was perceived as a «Russia's backyard». In the second half of the 1990-s US policy in the region has become more active and strategic competition with Russia started to grow. However, Russia's strategic priority in the region was contested only partially. After 9/11 American strategy in the region has become quite aggressive, geopolitical competition with Russia (and, partially, with China) has peaked during the «color» revolutions and then during Russian-Georgian war in 2008. During Obama's presidency serious attempts to establish a dialogue with Russia and China have been made. Post-Soviet space has partially lost its priority due to its connection with European dimension of American policy, while Afghan dimension is still a key factor determining American strategy in Central Asia. Now we are on the threshold of a new period in American policy, which is connected to the withdrawal from Afghanistan.